Electrochemical Validation of In-Cell Chromium Getters to Mitigate Chromium Poisoning in SOFC Stack. Issue 13 (3rd October 2017) - Uddin, Md Aman; Aphale, Ashish; Hu, Boxun; Heo, Su Jeong; Pasaogullari, Ugur; Singh, Prabhakar
Abstract : A porous, electrically conductive getter layer, consisting of mixtures of metal oxide getter and an electrically conducting perovskite phase, has been fabricated for incorporation in between the cell interconnect and the cathode to capture gaseous chromium species. Getter layer has been electrochemically tested in half-cell configuration in the presence of chromium vapor (Cr2 O3 /Air-3% H2 O) at 850°C for 100 hours. The electrochemical performance remains stable as evidenced by stable current density (I-t) at 0.5 V applied bias and EIS data obtained during the test. Tested cells were analyzed for the composition of reaction products and changes in the morphology. The gaseous chromium predominantly concentrated at the impinging getter surface, and the bulk electrode and electrode-electrolyte interface remained free of chromium.